Comparative Chromosome Mapping of U2 snRNA and 5S rRNA Genes in Gymnotus Species (Gymnotiformes, Gymnotidae): Evolutionary Dynamics and Sex Chromosome Linkage in G. pantanal - Utsunomia, Ricardo [UNESP]; Scacchetti, Priscilla C. [UNESP]; Pansonato-Alves, Jose C. [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Karger, 2014)
A comparative mapping of U2 small nuclear RNA (snRNA) and 5S ribosomal RNA (rRNA) genes was performed in 6 Gymnotus species. All species analyzed presented the U2 snDNA organized in conspicuous blocks and not co-located with rRNA genes. In addition, 5 species showed the U2 snDNA located in a single pair of chromosomes, which seems to be a conserved trait in this genus. Conversely, G. pantanal was the only species displaying several terminal signals in different chromosome pairs, including the X 1 sex chromosome but not the Y chromosome. This is the first report of U2 snRNA genes in sex chromosomes of fishes. The absence of sites in the Y chromosome of G. pantanal indicates a possible loss of terminal segments of the chromosomes involved in the Y formation. (C) 2014 S. Karger AG, Basel
Keywords: FISH; Molecular cytogenetics; Multigene family; Sex chromosomes; Teleostei